Observation of fractional Stokes-Einstein behavior in the simplest hydrogen-bonded liquid. - Fernandez-Alonso, F; Bermejo, F; McLain, SE; Turner, J; Molaison, J; Herwig, K (2007)
Quasielastic neutron scattering has been used to investigate the single-particle dynamics of hydrogen fluoride across its entire liquid range at ambient pressure. For T>230 K, translational diffusion obeys the celebrated Stokes-Einstein relation, in agreement with nuclear magnetic resonance studies. At lower temperatures, we find significant deviations from the above behavior in the form of a power law with exponent xi=-0.71+/-0.05. More striking than the above is a complete breakdown of the Debye-Stokes-Einstein relation for rotational diffusion. Our findings provide the first experimental verification of fractional Stokes-Einstein behavior in a hydrogen-bonded liquid, in agreement with recent computer simulations [S. R. Becker, Phys. Rev. Lett. 97, 055901 (2006)10.1103/PhysRevLett.97.055901].